FRI0465 Quantitative assessment of interstitial lung disease in idiopathic inflammatory myopathies: visual score and computerised processing analysis of high resolution computerised tomography. (12th June 2018) - Barsotti, S.; Romei, C.; Cioffi, E.; Perrone, E.; Giovannetti, C.; Mosca, M.; Falaschi, F.; Neri, R.
Abstract : Background: High resolution computed tomography (HRCT) is an essential technique for the characterisation of interstitial lung disease (ILD) in patients with idiopathic inflammatory myopathies (IIM). Although several visual scores are available for a semiquantitative evaluation of ILD, an automatic quantitative analysis of lung involvement may represent a valuable improvement to reproducibly determine the extent of the disease. Objectives: To compare the semiquantitative visual score to a volumetric texture and local volumetric histogram feature-based analysis software (CALLIPER) to quantify the lung involvement in IIM patients. Methods: 21 consecutive IIM patients (Bohan and Peter criteria) who underwent a HRCT between November 2016 and November 2017 were prospectively enrolled. Twelve were affected by polymyositis and 9 by dermatomyositis. We collected smoking habits data and myositis specific autoantibodies positivity, respiratory symptoms according to MRC dyspnea scale and two patients reported outcome questionnaires: Leicester cough questionnaire (LCQ) and St. George's Respiratory questionnaire (SGRQ). Patients underwent a non-contrast, supine, volumetric CT (≤2 mm slice thickness) that was evaluated by an expert radiologist according to Warrick's score (WS) and also quantified by CALLIPER (Mayo Biomedical Imaging Resource – USA). CALLIPER analysis of the extent of interstitial lung abnormalities (ground glass, lung reticulation, honeycombing) was performed and a total score, expressed as percentage of lung involved (ILD%), was obtained. Analysis of the vascular involvement were performed as percent of pulmonary vessel volume (VESS%). Results: Between the 21 patients, five (23.8%) were smokers. Four patients were positive for anti-synthetase autoantibodies -ASS (3 Jo-1, 1 Pl-7), 1 SRP, 1 Mi2. Dyspnea was present in 19 patients (90%): 9 grade 1, 7 grade 2, 3 grade 3 according to MRC scale. There were strict correlations between WS and ILD (r=0.802 p<0.001) and VESS% (r=0.746 p<0.001). LCQ score was negative correlated to WS (r=−0.728 p=0.007) but the correlations were stricter with ILD score (r=−0.868 p<0.001) and VESS% (r=−0.801 p<0.002). SGRQ did not correlate both to WS and CALLIPER parameters. Patients with ASS have higher ILD and VESS% compared to seronegative patients (respectively p=0.003 and p=0.006). Conclusions: CALLIPER represents an innovative technique to quantify the lung involvement in IIM patients: the main advantage of CALLIPER is the reproducibility that avoids the inter and intra-reader bias. Although more data are needed in larger cohorts, the use of CALLIPER may open new routes for the evaluation of ILD in IIM patients, both in medical practice and in randomised controlled trials. Disclosure of Interest: None declared